DYNAMICS OF CHANGES IN BLOOD PRESSURE DISEASES ON THE TERRITORY OF UZBEKISTAN DUE TO WEATHER CHANGES - Tillyakhodjaeva, Z.D.; Dergacheva, I.V.; Quranboyeva, Z.E.; Mirvaliyeva, N.R.; Jumamuratov, A.; Sultashova, O.G. (SCIENCE and SOCIETY, 2024)
To date, one of the important issues is the study of the sensitivity of the population to weather conditions, in this study, the change in the incidence of blood pressure of the population throughout the Republic of Uzbekistan in the past 10 years was studied. According to the obtained results, the population in Uzbekistan has various blood pressure disorders in different regions, the indicators of which are registered as increasing.
Keywords: the territory of Uzbekistan; weather sensitivity; diseases; blood pressure; sensitivity to weather; climatic changes